Comparative Evaluation of Ketamine-Diazepam and Tiletamine-Zolazepam Induction Anaesthesia with Isoflurane Maintenance in Dogs - Bhayla, Ziyad M; Dabas, Vijander Singh; Suthar, Dipal N; Jhala, Shivraj K; Didugu, Mohitha Sree (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
The present anaesthetic study was conducted in twelve dogs requiring general anaesthesia for surgical procedures, which were randomly divided into two groups. Induction of anaesthesia was achieved by intravenous administration of tiletamine @ 2.5 mg/kg b.wt. with zolazepam @ 2.5 mg/kg b.wt. in group I, and ketamine @ 5 mg/kg b.wt. with diazepam @ 0.5 mg/kg b.wt. in group II and then maintained by isoflurane in both groups. Anaesthetic, clinico-physiological and haemato-biochemical parameters were evaluated at different time intervals. The tiletamine-zolazepam combination showed better induction quality than the ketamine-diazepam combination, although both combinations had fair to excellent quality. Excellent maintenance quality anaesthesia with smooth and rapid recovery was observed with isoflurane. Non-significant differences were found in haemato-biochemical parameters between the groups and between time periods post-induction. However, significant differences were recorded in clinico-physiological parameters within the groups at different time periods.Few complications were encountered during induction and maintenance in both groups.